Pengembangan Media Box of Number Berbasis Tematik untuk Pembelajaran Matematika Permulaan Anak Usia 4-5 Tahun - Ulfah, Maulidya; Nurhayati, Eti; Abyati, Hindun (Al-Athfal: Jurnal Pendidikan Anak, 2019)
Media plays to improve in achieving a learning goal because it can help teachers deliver learning material quickly. This research develops thematic-based box of number media that aims to introduce the beginning of mathematics to children aged 4-5 years so that it can delight children in learning. The resulting media include three themes, names of plants, myself, and the universe. This type of research used in this research is Research and Development (RnD). The results showed that the media box of number obtained an assessment from media experts with the criteria of feasible, namely the percentage of 92.5%, which previously earned 62.5%. Assessment by material experts get "decent" standards, with a percentage of 97.5% from 62.5% previously. While the results of the evaluation by users get the criteria "feasible" with a percentage of 95%. These results can be concluded that the thematic-based box of number media is suitable for beginning mathematics learning in children aged 4-5 years.